Credit Risk Analysis at PT BPR Bank Boyolali: A Case Study on Micro Business Sector - Amanda Khoirun Nisa; Moh. Indra Bangsawan (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze credit arrangements and risk management strategies at PT BPR Bank Boyolali, focusing on the microbusiness sector. To support financial inclusion, PT BPR Bank Boyolali provides credit to micro businesses, which often face challenges due tolimited collateral, income fluctuations, and economic instability. This study employs a qualitative approach with descriptive analysis method to examine the lending process, risk mitigation policies, and the impact of credit risk on the financial health of PT PR Bank Boyolali. The results showed that PT BPR Bank Boyolali implemented a creditworthiness assessment system based on the 5C method. The bank also diversified its loan portfolio and provided financial education to customers to mitigate credit risk. Additionally, the bank applies flexible policies tailored to the capacity of micro businesses. However, this study also identified challenges in risk management related to the instability of micro businesses. Based on these findings, PT BPR Bank Boyolali is recommended to continue developing digital risk assessment technology and strengthening risk mitigation strategies to maintain financial health and support microenterprise sustainability. This research contributes to our understanding of credit risk management practices in rural banks, especially when lending to micro businesses.